Telescoped Continuous Flow Synthesis of 2-Substituted 1,4-Benzoquinones via Oxidative Dearomatisation of para-Substituted Phenols Using Singlet Oxygen in Supercritical CO2 - Abreu, Bruna L.; Boufroura, Hamza; Moore, Jonathan C.; Poliakoff, Martyn; George, Michael W. (Synthesis, 2022)
This paper describes a continuous multi-step synthesis in supercritical CO2. A continuous flow synthesis of 2-substituted 1,4-benzoquinones is reported, and details of the high-pressure reactors are given. This proceeds via the telescoped dearomatisation of p-substituted phenols using singlet oxygen in supercritical CO2 and an acid-mediated C–C migration. The process has a short residence time of 30 minutes, with overall yields and projected productivities of up to 83% and 9 g/day, respectively. This methodology enables a safe and efficient synthesis of 2-substituted 1,4-benzoquinones from photo-generated singlet oxygen, and cheap and readily available p-substituted phenols. The procedure has high atom efficiency, low photocatalyst loading, and substitutes potentially hazardous and corrosive reagents and solvents for molecular oxygen, CO2, and the less hazardous solid-supported acid Amberlyst-15.
Keywords: singlet oxygen; photooxidation; continuous flow; supercritical CO2; telescoped synthesis; dearomatization; para-substituted phenols; 1,4-benzoquinones